1984
DOI: 10.1104/pp.75.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthate Partitioning in Split-Root Citrus Seedlings with Mycorrhizal and Nonmycorrhizal Root Systems

Abstract: Photosynthate partitioning was examined in seedings of sour orange (Citrus aurantium L.) and Carrizo citrange (Poncirus trifoliata jL.j Raf.x C. sinensis [L.] Osbeck) grown with split root systems inoculated on one side with vesicular-arbuscular mycorrhizal fungus (Glomus intraradices Schenck and Smith). Source-sink relations were studied without mitipting differences in mineral content or physiological age that can occur in separate plant comparisons, because phosphorus was evenly distributed between leaves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
4
6

Year Published

1986
1986
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 21 publications
8
79
4
6
Order By: Relevance
“…Hirrel & Gerdemann (1980) found that NaCl at 12 g kg~^ soil reduced colonization of onion and bell pepper plants from the typical, respective values of 55 to 70% and 60 to 80% for non-salinized plants to only 15 to 40% and 5 to 20%,. The 53% colonization at the highest salt concentration in the present study was still at a level considered adequate for mycorrhizal enhancement of plant growth (Koch & Johnson, 1984) and in fact showed a substantial beneficial effect even at this reduced level (Pigs 2 and 3).…”
Section: Mycorrhizal Colonizationmentioning
confidence: 83%
See 2 more Smart Citations
“…Hirrel & Gerdemann (1980) found that NaCl at 12 g kg~^ soil reduced colonization of onion and bell pepper plants from the typical, respective values of 55 to 70% and 60 to 80% for non-salinized plants to only 15 to 40% and 5 to 20%,. The 53% colonization at the highest salt concentration in the present study was still at a level considered adequate for mycorrhizal enhancement of plant growth (Koch & Johnson, 1984) and in fact showed a substantial beneficial effect even at this reduced level (Pigs 2 and 3).…”
Section: Mycorrhizal Colonizationmentioning
confidence: 83%
“…x Citrus sinensis (L.) Osbeck] seedlings were grown as described by Koch & Johnson (1984). Seedling root halves were potted into two 500 ml square plastic containers joined together along one side.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been demonstrated and discussed for VA mycorrhizas (Koch & Johnson, 1984;Koide &: Elliot, 1989;Jakobsen & Rosendahl, 1990) as well as for ectomycorrhizas (Reid, Kidd & Ekwebelam, 1983;Finlay & Read, 1986a). The experiments of Miller, Durall & Rygiewicz (1989) are of particular interest for the interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%
“…One-half of the root system from the cluster of tillers was placed on each side of the split-root apparatus (Fig. 1), modelled on that of Koch & Johnson (1984).…”
Section: Materials and Mi'thodsmentioning
confidence: 99%